Procedural outcomes and learning curve of cardiac arrhythmias catheter ablation using remote magnetic navigation: Experience from a large‐scale single‐center study. Issue 9 (26th May 2020) - Li, Xiang; Jin, Qi; Zhang, Ning; Ling, Tianyou; Lin, Changjian; Jia, Kangni; Bao, Yangyang; Xie, Yun; Wei, Yue; Chen, Kang; Pan, Wenqi; Xie, Yucai; et al.
Abstract: Background: Remote magnetic navigation (RMN)‐guided ablation has become an inspiring method of catheter ablation for tachyarrhythmias. Hypothesis: Data from a large‐scale single center may provide further insight into the safety of and the learning curve for RMN‐guided ablation. Methods: A total of 1003 catheter ablation procedures using RMN for conditions including supraventricular ventricular tachycardia, atrial tachyarrhythmias, and premature ventricular contraction/ventricular tachycardia (PVC/VT) were retrospectively analyzed from an ablation registry. Procedural outcomes, including procedure time, mapping time, X‐ray time, and RF time, were assessed. The complications were classified into two categories: major and minor. A subanalysis was used to illustrate the learning curve of RMN‐guided ablation by assessing procedure time and total X‐ray time of 502 atrial fibrillation (AF) ablation procedures. Results: Among these procedures, 556 (55.4%) were AF and 290 (28.9%) were PVC/VT. Electrical pulmonary vein isolation was achieved in 99.0% of AF procedures, and acute success reached 90.3% in PVC/VT procedures. The overall complication rate was 0.5%. In the subanalysis of AF procedures, the overall procedure time and X‐ray time of procedures were short (125.9 ± 54.6 and 5.3 ± 3.9 minutes, respectively) and proceeded to decrease from the initial 30 procedures to about 300 procedures, where the learning curve reached plateau, demonstrating maximum procedure efficiency. Conclusions: RMN‐guided ablation is safe, as verified by very low overall complication rate and reduced X‐ray time. In our study, even the first AF procedures had a relatively low procedure time and total X‐ray time, and procedure efficiency improved during the learning curve.